Kualitas Pelayanan Publik Pada Pembuatan Kartu Tanda Penduduk (KTP) : Studi Di Dinas Kependudukan Dan Pencatatan Sipil Kota Batu - Lestari Widi (Prodi Ilmu Administrasi Negara, 2022)
The government's main task is to provide public services to service recipients. Public services are service providers by the government, both private and public, using financing or free use to meet the needs or interests of the community. The purpose of this study was to determine the Quality of Service in Making Identity Cards (KTP) at the Population and Civil Registration Office of Batu City, as well as to determine the supporting and inhibiting factors of Service Quality in Making Identity Cards (KTP) at the Population and Civil Registration Office of Batu City. The type of research used is qualitative research. Source of data obtained from primary and secondary data. Data collection techniques using observation, interviews, and documentation. The informant's technique is Snowball sampling using a key informant who is the Head of the Population Identity Section at the Population and Civil Registration Office of Batu City. The data analysis technique uses reduction, presentation, and conclusion drawing. The validity of the data used is technical triangulation. The results of the study find out that the quality of service in making identity cards (KTP) can be said to be good in terms of dimensions, meaning that the dimensions of tangible, reliability, responsiveness, assurance, and empathy are by service standards. Thus, those who support the service of making Identity Cards at the Population and Civil Registration Office of Batu City are from the dimensions of Reliability, Responsiveness, Assurance, and Empathy because of the availability of adequate facilities such as the presence of mobile cars, ball pick-ups, and PKK Peak to facilitate the community in managing population documents and the service process provided quickly and quickly as well as the courtesy of employees. The sign of the obstacle is the Tangible dimension because there are still several problems in making Identity Cards, such as the network that often occurs in errors, the unavailability of special waiting room facilities for the disabled and the elderly, and the lack of identity cards